Utilization of Aralle River Aggregate, Buntu District, Malangka as a Concrete Mixture Material - Faisal Ical Alnaldi; Herman Parung; Benny Kusuma (Paulus Civil Engineering Journal, 2022)
Development in Buntu Malangka District is increasingly rapid, especially in the field of development, so the use of concrete becomes the main choice as a building construction. Construction in the field of concrete construction used in the area uses more aggregates derived from rivers. The Aralle River, which is one of the major and closest rivers in the area, is the main location for people to take aggregates, and no previous research has been done on the level of aggregate resistance when used as a concrete mix. The purpose of this study was to find out the aggregate characteristics of the Aralle River and its strength in concrete work. Powerful press plan 20 MPa using the American Concrete Institute method. Cylindrical test object 15 cm diameter 30 cm high for strong testing press 12 pieces and strong pull 3 pieces and beams 60 × 15 cm, strong test bending 3 pieces. Based on the results of the study obtained on the average concrete press strength test at the age of 7, 14, 21, 28 days each amounted to 9,903 MPa, 15,468 MPa, 18,203 MPa, 21,126 MPa. At the age of 28 days obtained strong tensile 2,028 MPa, strong bending 2,756 MPa and Modulus elasticity 21252,778 MPa. Based on the results of the study it can be concluded that the characteristic value and strong testing press at the age of 28 days obtained the value of meeting and achieving the planned quality so that the aggregate is well used in concrete construction.